2008
DOI: 10.1002/ijc.23608
|View full text |Cite
|
Sign up to set email alerts
|

The aberrant methylation of TSP1 suppresses TGF‐β1 activation in colorectal cancer

Abstract: Colorectal cancer arises from the progressive accumulation of mutations and epigenetic alterations in colon epithelial cells. Such alterations often deregulate signaling pathways that affect the formation of colon cancer, such as the Wnt, RAS-MAPK and TGF-b pathways. The tumor promoting effects of mutations in genes, such as APC, have been demonstrated in cancer cell lines and in mouse models of intestinal cancer; however, the biological effects of most epigenetic events identified in colorectal cancer remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 40 publications
0
48
2
Order By: Relevance
“…Tumors from patients that expressed high levels of TSP-1 and had low MVD counts were more likely to exhibit a decrease in angiogenesis compared to control tissue. The inverse has also been documented; a decrease in TSP-1 expression was accompanied with high MVD counts which may contribute to an angiogenic phenotype [31,39,40]. In the present study, we failed to demonstrate any correlation between TSP-1 expression, MVD and VEGF expression.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Tumors from patients that expressed high levels of TSP-1 and had low MVD counts were more likely to exhibit a decrease in angiogenesis compared to control tissue. The inverse has also been documented; a decrease in TSP-1 expression was accompanied with high MVD counts which may contribute to an angiogenic phenotype [31,39,40]. In the present study, we failed to demonstrate any correlation between TSP-1 expression, MVD and VEGF expression.…”
Section: Discussioncontrasting
confidence: 54%
“…These results may be due to the difference in TSP-1 products produced by tumor cells or to different antibodies used. Rojas et al, suggested that the tumor cells are a major source of TSP-1 and that methylation of TSP-1 substantially reduces TSP-1 activity in the tumors of the colon [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,12,13 In colorectal cancers, for example, where the TGF-b/BMP signaling pathway in general negatively regulates tumor cell proliferation from early carcinogenesis to a later progression stage, loss-of-function mutation in TGF-b/BMP signaling, such as the inactivating mutation of SMAD4, has frequently been identified as an important early carcinogenic event. 10,14,15 On the other hand, in various types of cancers especially at later cancer progression stages, TGF-b/BMPs, frequently produced by cancer cells themselves, promote angiogenesis and epithelial-to-mesenchymal transition (EMT). Furthermore, in a certain subset of aggressive cancers, the TGF-b/BMP signaling pathway often promotes cancer cell invasion and migration in an autocrine and paracrine manner.…”
Section: Uiccmentioning
confidence: 99%
“…Glioblastomas, for instance, are typically characterized by excessive blood vessel development and frequently display epigenetic inactivation of the anti-angiogenic thrombospondin-1 (THBS-1) gene (Li et al, 1999). THBS-1 is also suppressed early in breast carcinogenesis by histone modifications (Hinshelwood et al, 2007) and THBS-1 silencing through methylation is observed in a significant portion of primary colorectal adenomas (Rojas et al, 2008). Interestingly, oxygen-glucose deprivation, which frequently occurs in tumors, was shown to increase THBS-1 promoter methylation and subsequent silencing.…”
Section: Epigenetic Therapy Targeting Tumor Angiogenesismentioning
confidence: 99%